Esej in narava literarnovednega diskurza - Virk, Tomo (Primerjalna književnost, 2010)
The study of literature may take place in the form of generalizations, typologies, classifications, numerical approaches, and so on, or - especially when this concerns issues of literariness - in the form of essays. The discourse characteristic of essays in literary studies opens up those segments of literature that are not accessible to discourse that is oriented towards "objectivizing" disciplines.
Keywords: literarna veda; literary science; literarna znanost; esej; singularnost; literarnost